KOMIK “PADE TOLAK STUNTING” EFEKTIF UNTUK MENINGKATKAN PENGETAHUAN PENCEGAHAN STUNTING PADA REMAJA SEBAGAI CALON PENGANTIN DI LOMBOK TENGAH - Diarti, Maruni Wiwin; Jiwintarum, Yunan; Duarsa , Artha Budi Susila; Anulus, Ayu (Media Penelitian dan Pengembangan Kesehatan, 2024)
This study aimed to develop comic "Pade Tolak Stunting" on increasing the knowledge of female adolescents related to infectious diseases (worms, diarrhea, malaria, and ARI) as risk factors for stunting. This study was a pre-experimental study with a pre-post-test with control group design. The study subject was female adolescents (10-19 years old.) in Dusun Sade, Central Lombok. A total of 23 female adolescents were involved in this study. The comic media "Pade Tolak Stunting" was developed in the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data were analyzed using the Wilcoxon Rank Test. After tested, media is applicable for stunting education media. The results showed that there was an increase in the knowledge of prospective brides and grooms about infectious diseases as risk factors for stunting in Dusun Sade, Central Lombok (p <0.001). The conclusion is that the comic "Pade Tolak Stunting" is feasible and also can increase the knowledge of female adolescents about infectious diseases as risk factors for stunting.